Review of Aferos Kazantsev (Coleoptera, Lycidae), with a note on Staepteron cyanoxanthum (Bourgeois) - Kazantsev, Sergey V. (Zootaxa, 2005)
The genus Aferos Kazantsev is redescribed and six new species, A. endroedyi sp. n., A. natalensis sp. n., A. rubellus sp. n., A. silvestris sp. n., A. transvaalensis sp. n. and A. youngai sp. n. are described from South Africa. A key to all 18 known species of Aferos is provided. Aferotini Kazantsev, 2004, syn. n. is synonymized with Slipinskiini Bocák et Bocáková, 1992. Staepteron cyanoxanthum (Bourgeois) is illustrated, and the genus Staepteron Kazantsev is tentatively placed in Flagraxina (Dictyopterini, Erotinae).